Isomeric and ground state energy level measurements of natural tellurium isotopes via (γ,n) reaction - Tamkas, M.; Akcali, O.; Durusoy, A. (IOP PUBLISHING LTD, 2015)
We have planned to measure isomeric and ground state energy levels in Te-120(gamma,n)Te-119m,Te-g, Te-122(gamma,n)Te-121m,Te-g, Te-128(gamma,n)Te-127m,Te-g, Te-130(gamma,n)Te-129m,Te-g photonuclear reactions of natural tellurium induced by bremsstrahlung photons with end-point energy at 18 MeV. The sample was irradiated in the clinical linear electron accelerator (Philips SLi-25) at Akdeniz University Hospital. The gamma spectrum of the tellurium sample was measured using HP(Ge) semiconductor detector (ORTEC) and multi channel analyzer. We used both MAESTRO (ORTEC) and home made root based gui program (Theia) for data analyzing. The obtained experimental data values are compared with NUDAT energy values.
Keywords: isomeric state; ground state; energy level; EXCITATION; ACTIVATION; Astronomy & Astrophysics; Physics